Molecular characterization of sheep and human isolates of Echinococcus granulosus from temperate region of India - BEIGH, A B; DARZI, M M; BASHIR, S; DAR, P A; BHAT, B A; NAZKI, S; AHMAD, I (The Indian Journal of Animal Sciences, 2021)
The aim of the present study was to investigate Echinococcus granulosus genotypes in the Kashmir valley. A total of 2,100 sheep and human patients were screened for the presence of hydatidosis. Total 87 isolates were collected, 85 from sheep and 2 isolates from human beings. The rDNA-ITS1 fragment were amplified with BD1 / 4S primers. In addition, fragments of genes coding for ITS1 were sequenced. The length of amplified fragment for all isolated samples with sheep origin was 1,000 bp and with human origin was between 1,000 bp and 1,100 bp. The products on digestion with restriction enzymes Rsa 1, Alu 1, Msp 1 yielded identical fragments, 300 and 700 bp in sheep and 325 and 700 bp in humans. Intact 1000 bp fragment was observed with Taq 1. The molecular findings reveal that sheep strain (G1) is the predominant genotype in sheep and humans in Kashmir valley.